Lock-in Thermography Basics and Use for Evaluating Electronic Devices and Materials - Breitenstein, Otwin; Warta, Wilhelm; Langenkamp, Martin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book deals with lock-in thermography (LIT) as a special active dynamic variant of the well-known IR thermography. It enables a much improved signal-to-noise ratio (up to 1000x) and a far better lateral resolution compared to steady-state thermography. The book concentrates on applications to electronic devices and materials, but the basic chapters are useful as well for non-destructive evaluation. Various experimental approaches to LIT are reviewed with special emphasis to different available commercial LIT systems. New LIT applications are reviewed, like Illuminated LIT applied to solar cells , and non-thermal LIT lifetime mapping. Typical LIT investigation case studies are introduced.
Introduction -- Physical and Technical Basics -- Timing Strategies -- Heat Dissipation Mechanisms in Solar Cells -- Carrier Density Imaging -- Illuminated Lock-in Thermography (ILIT) -- Experimental Technique -- Theory -- Measurement Strategies -- Typical Applications -- Summary and Outlook.
Keywords: Physics; Engineering; Materials; Surfaces (Physics).; Physics; Optics, Optoelectronics, Plasmonics and Optical Devices; Characterization and Evaluation of Materials; Engineering, general; Structural Materials